2005
DOI: 10.1524/ract.93.5.273.64279
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and sorption of U(VI) in compacted bentonite studied by a capillary method

Abstract: Diffusion and sorption of U(VI) in compacted bentonite were studied using a capillary method. The experiments were carried out at room temperature in 0.1 M NaClO 4 solutions at pH 7.0 ± 0.1. Effects of contact time, solution concentration and bentonite bulk density on diffusion were also investigated. The results fit the Fick's second law very well and are in good agreement with the literature data for similar bentonite dry densities [3]. The K d values from capillary method are in most cases lower than those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 14 publications
3
29
1
Order By: Relevance
“…From Figure 5, it is clear that the K d values calculated from the D e value for HTO and the D a value for the Cs + ion were much larger than those deduced from n 0 and n slice 1 . Wang et al (2005b) studied the diffusion of U(VI) in compacted bentonite and found similar results. The data listed in Table 1 indicate that the D e value for the Cs + ion was much higher than that of HTO, thereby suggesting that the diffusion of the Cs + ion was mainly dominated by surface diffusion (Yu and Neretnieks 1997;Wang and Liu 2004d).…”
Section: Sorption Of Radiocaesium Onto Powdered and Compacted Rectorimentioning
confidence: 62%
See 3 more Smart Citations
“…From Figure 5, it is clear that the K d values calculated from the D e value for HTO and the D a value for the Cs + ion were much larger than those deduced from n 0 and n slice 1 . Wang et al (2005b) studied the diffusion of U(VI) in compacted bentonite and found similar results. The data listed in Table 1 indicate that the D e value for the Cs + ion was much higher than that of HTO, thereby suggesting that the diffusion of the Cs + ion was mainly dominated by surface diffusion (Yu and Neretnieks 1997;Wang and Liu 2004d).…”
Section: Sorption Of Radiocaesium Onto Powdered and Compacted Rectorimentioning
confidence: 62%
“…The data listed in Table 1 indicate that the D e value for the Cs + ion was much higher than that of HTO, thereby suggesting that the diffusion of the Cs + ion was mainly dominated by surface diffusion (Yu and Neretnieks 1997;Wang and Liu 2004d). Equation (7) can only be used when the diffusion mechanism of the radionuclide is the same as that of HTO (Wang et al 2005b).…”
Section: Sorption Of Radiocaesium Onto Powdered and Compacted Rectorimentioning
confidence: 99%
See 2 more Smart Citations
“…Sorption of diffusing species changes the pore space in Opalinus clay and may have a significant beneficial impact on the long-term diffusivity (Wang et al 2005). The macroscopic diffusivity of the system with and without sorption is different (Korichi et al 2010).…”
mentioning
confidence: 99%